Avanços e entraves do plano agricultura de baixo carbono em Goiás - Rosa, Cinthia Guimarães (2018)
Public policies can be defined as the field of knowledge that seeks, at the same time, to put ‘the government into action’ and/or analyze this action and, when necessary, propose changes in the direction of this action. The process of production and diffusion of innovations in agriculture has completely changed its nature, incorporates beyond the "old demands", new social and environmental imperatives. It is a huge challenge nowadays, as it opposes different social and economic interests (rural and not rural). Considering the issue of climate change, it even goes beyond national borders, with Brazil positioning and committing itself to international organizations on this issue. In this context, the ABC Plan (Low Carbon Agriculture) presents goals and strategies for Brazilian agriculture. Therefore, the aim of this study is to analyze the advances and impacts of the adoption of the ABC Plan in Goiás. Also, to give an understanding of the disbursements of the ABC Program in the sustainable development of the agricultural of Goiás. The research was developed with qualitative and quantitative methods, with the contribution of a Geographic Information System (GIS). In order to understand the efficiency in the use of ABC Program resources, an analysis was carried out in Nova Crixás. This city was the first place in access to the resources of the ABC Program and the largest cattle herd in Goiás. The intention was to identify, through the pasture quality maps, land use, Permanent Preservation Area (PPA) and Legal Reserve (LR) and environmental vulnerability; and interviews, implementation actions, changes in the production pattern and the environmental quality of the region. The land use maps were generated for the year 2010, therefore prior to the Low Carbon Agriculture Policy, and for the year 2016, after the implementation of the public policy. Regarding the results, Goiás and Nova Crixás invested mainly in pasture recovery (the rates of degraded pastures in New Crixas confirm this demand). However, the few changes (2%) in the territory still do not reflect the efficiency in the investments. The interviews also indicate an institutional environment not too much motivator and the presence of conservative businesspersons in Nova Crixás. The interviews with producers also indicate a not too much motivator and conservative institutional environment.